Persecution, Collaboration, Resistance. Music in the ‘Reichskommissariat Norwegen’ (1940–45) - Rupprecht, Ina (2020)
When Germany invaded Norway on 9 April 1940, the long lasting bilateral relations changed fundamentally. Immediately, the administration of the ‘Reichskommissariat Norwegen’ (responsible for culture and therein music together with the Norwegian puppet regime’s department for culture) implemented the adaption to the new, official National Socialist guidelines. The diversity of music in Norway during the occupation is presented in this book by Norwegian and German authors, confronting research on collaboration, persecution, and resistance for the first time as an international endeavour. The different essays illustrate not only examples of exile and persecution and ask for the consequences of Nazi politics on prominent and forgotten fates, but depict how Norwegian artists and their organisations positioned themselves towards collaboration or resistance during and after the war, as well as contrasting it with the impressions of German musicians, both military and civilian, playing in Norway during the occupation. Including Norway into the international discourse on ‘Music and Nazism’, the articles address readers both interested in the German occupation of Norway, and the implications the German administration and its Norwegian counterparts had on the music life.